Running the U.S. Economy at Full Throttle Is a Stressful Variant of Capitalism - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2022)
Maximizing output without taking into consideration the negative externalities generated, including the harm to the mental and physical health of the population creates psychological stress. Focusing on the bellwether indicators of economic performance including working more, generating income, accepting more risks, while disregarding its effect on work-life balance, on income distribution, and the quality of life in general creates stressors that harm the human biological system. Stress is the biological reaction to external stimuli that threatens the self-preservation instinct of a human organism. The stress was generated by debilitating poverty, financial insecurity, by the highest level of inequality among rich countries that led to the hollowing out of the middle class, by the lack of social safety nets that might have mitigated the turbulence of adjusting to a knowledge economy, by the downward social mobility of millions disadvantaged by globalization, and by the inadequate retraining opportunities that prevented those displaced by the penetration of imports to find employment in the expanding IT sector. These stressors have been accumulating in the U.S. population for decades, as indicated by the deterioration of mental health, by the propensity to relieve the pain through the use of illicit drugs, by deaths of despair, by the incarceration rate, by mass murders, by the fall in life expectancy, by the attenuation in life satisfaction, and by the rise of populism, creating many mental, biological, social, economic, and political quandaries.
Keywords: A14; D60; D91; E71; G41; P16; 330; capitalism; psychological stress; globalization; financial crisis; inequality; populism